Thin Layer Chromatography of Aryl Hydroxy Compounds and Their Metal Complexes - Kulkarni, G.B.; A. Shaikh, Kabeer; Patel, N.T. (Asian Journal of Chemistry, 2010)
Thin layer chromatographic study of L2 = 2´-(2-hydroxy phenyl)-benzothiazolyl hydrazone, L2 = 2´ (2-hydroxy-5-chloroacetophenyl)-benzothiazolyl hydrazone, L3 = 2´-(2,5-dihydroxyacetophenyl-benzothiazolyl hydrazone and their complexes have been made using silica gel as adsorbent, benzene: acetone as developing media.